(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
In order to understand the control by rules in therapy, the study verified the presence of orientation and self-orientation in sessions held by experienced and less experienced behavior-analytic therapists and if there were differences in their degree of specificity. Orientation meant indication given by the therapist outside the therapy session. When issued by the client, self-orientation was registered. Six less experienced and six experienced therapists participated in the study. Each recorded three sessions of three adult clients who had no specific diagnostic. The experienced behavior therapists presented a wide variation in the use of orientation among clients and sessions and in average they oriented more than the less experienced. The majority of the experienced behavior therapists clients self-oriented more than those of the less experienced. Orientation and self-orientation for specific action prevailed. One or more orientations and self-orientations occurred in sessions conducted by behavior-analytic therapists, suggesting that emission and rule alterations can lead to change in the therapeutical process.